Banking Service Usage Patterns among Customers in Nepal: Evidence from Public and Private Banks - Neupane, Sangam; Mittal, Anubhav (International Journal of Atharva, 2026)
Background: Banks are fundamental to modern financial systems, yet the increased availability of banking services does not guarantee their effective or diversified use. A critical distinction exists between service availability (institutional supply) and service usage (customer behavior). In developing countries like Nepal, rapid digitalization and the presence of diverse bank ownership structures (public and private) create a complex landscape. While financial literacy is known to influence financial decisions, empirical research on actual behavioral usage patterns across different banking services—savings, credit, investment, and transactions—remains scarce, particularly in the context of Nepal’s post-digital expansion era. Objectives: The main objective of this study is to assess the availability and usage behavior of banking services among financially literate customers in Nepal, with a specific focus on comparing patterns between public and private sector banks. It aims to move beyond access-based indicators to analyze actual customer engagement across multiple financial dimensions. Methods: The study employed a descriptive and analytical research design based on primary data collected during a doctoral research pre-test phase. Data was gathered from 30 banking customers in Nepal using a structured questionnaire. Respondents were categorized by bank type (public or private). The analysis, conducted using SPSS, involved frequency distributions, descriptive statistics, cross-tabulation, chi-square tests, and independent samples t-tests to examine differences in savings, credit, investment, and transaction behavior between the two customer groups. Findings: The pre-test analysis revealed several key insights: • Digital Dominance: Digital banking is the dominant transaction mode, with 90.3% of respondents using digital channels. Public bank customers showed a slightly higher reliance (94.4%) than private bank customers (84.6%). • Prudent but Moderate Usage: Respondents demonstrated responsible loan and credit behavior (Mean = 3.95) and strong trust in formal banking. However, engagement was moderate for investment (Mean = 3.78) and lower for regular savings and account management (Mean = 3.60). • No Significant Institutional Differences: Independent samples t-tests showed no statistically significant differences between public and private bank customers in savings and account management, loan and credit behavior, or investment and risk behavior, suggesting that financial literacy may be a more influential factor than bank ownership type in this sample. Conclusion: The study concludes that financially literate customers in Nepal exhibit responsible but moderate-intensity banking service usage. While digital adoption is high and credit discipline is strong, savings consistency and investment participation lag. Critically, the lack of significant behavioral differences between public and private bank customers underscores the central role of financial literacy in shaping usage patterns, potentially outweighing institutional factors like ownership structure in the context of a financially aware customer base. Novelty: This research contributes to the literature by shifting the analytical focus from banking service access to behavioral usage patterns across multiple financial dimensions. It provides novel comparative empirical evidence on public versus private bank customers in Nepal, a context often overlooked in global banking research. Crucially, it explores how usage behavior manifests among financially literate customers, offering insights into the interplay between individual capability and institutional environment in a developing economy.